Optimization of Reservoir Potential through Floating Net Cages and Fish Farming Training - Prasetyo, Rian; Komariah, Ainur; Husein, Muhammad (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2025)
This community service program aims to optimize the reservoir potential in Karangasem Village, Sukoharjo Regency, through floating net cages and fish farming training. Addressing the lack of technical expertise among the "GP" Fish Farmers Group, the program enabled them to utilize the reservoir for economic and sustainable fish farming activities. The program encompassed three phases: preparation, implementation, and monitoring. During preparation, the necessary resources and permits were secured. The implementation phase featured interactive training on the design, construction, and maintenance of floating net cages and practical skills for gourami fish farming a species with high economic value. The program yielded significant improvements in participants' knowledge and skills. Pre- and post-training assessments demonstrated a 32.13% increase in knowledge, with average scores rising from 61.39 to 81.11. Participants successfully constructed operational floating net cages with technical specifications, including floating drums, iron frames, nets, and wooden pathways. Their active engagement during discussions and practice sessions highlighted enthusiasm for expanding gourami fish farming individually and collectively. The initiative emphasized practical solutions for utilizing the reservoir's freshwater efficiently and creating economic opportunities through aquaculture. Future recommendations include integrating digital marketing strategies to broaden the market reach of fish products and workshops on product innovation, such as ready-to-cook gourami or other fish-based items. Ongoing mentoring and periodic evaluations are essential to ensure the program’s sustainability and effectiveness. This program demonstrates the potential of community-driven aquaculture to enhance rural economic resilience and environmental sustainability.